Sistem Informasi Geografis Pemetaan Objek Wisata Wilayah Kota Sungai Penuh Berbasis Website - Sularno; Andre prasetyo (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
The author has conducted research on tourist objects in the city Sungai penuh with the aim of finding the location of tourist objects in the city of the river that is accessed via the web. Thus this geographical information system will display all the locations of attractions in the Sungai penuh city, it is expected that the results of the geographical information system for the location of attractions in the full river can be accessed via the internet using the web. From the results of the data collected, the author uses the Research Laboratory method, which is processing the results of research in a computer laboratory. From the results of this study the geographic information system designed for tourist attractions in the Sungai penuh based web area. It is hoped that this information system can be useful for people outside the full River city when they want to travel and also when the holidays arrive.